Optimal allocation of FACTS devices for improved economic dispatch in power systems - Deng, Wan Hong (2009)
Nowadays, Flexible AC Transmission Systems (FACTS) devices are utilized to overcome obstacles which power utility industries have faced such as environmental problem and escalating costs in upgrading their systems. Variable Series Capacitors (VSCs) and Static Phase Shifters (SPSs) are two kinds of devices in FACTS that have been widely accepted as likely solutions for alleviating the power transfer limitations seen in overstretched generation and transmission systems.